IDENTIFICATION OF STRESS, ANXIETY, AND DEPRESSION LEVELS OF STUDENTS IN PREPARATION FOR THE EXIT EXAM COMPETENCY TEST - Marsidi, Sitti Rahmah (Journal of Vocational Health Studies, 2021)
Background: Permendikbud No.2 of 2020 regulates student competency test in the health sector. The exit exam competency test is a requirement that must be met by students after completing all stages of education in order to get a certificate and Surat Tanda Registrasi (STR). The results of the preliminary study show that although there is a high chance of passing the exit exam competency test at the RMIK (Medical Records and Health Information) Study Program at Esa Unggul University (UEU), some of the students are not ready or not ready and feel negative in the form of anxiety, worry, fear. Purpose: To identify stress, anxiety, and depression levels of RMIK Esa Unggul University students in preparation for the exit exam competency test. 61 students who have met the requirements. Method: The measuring instrument used is the Depression Anxiety Stress Scale (DASS 42) which has been modified and adjusted. Result: Showed that more than half of the sample (50.8%) had normal stress, 10 students (16.4%) had severe stress, and 7 students (11.5%) had extremely severe stress. Almost half or about 25 (41%) students feel extremely severe anxiety in preparation for the exit exam competency test. On the other hand, about 14 (23%) students felt normal anxiety and 10 (16.4%) students felt moderate anxiety. More than half of the sample, namely 34 (55.7%) students felt depression at the normal level in preparation for the exit exam competency test. Conclusion: The highest level of stress felt by students in preparation for the exit exam competency test was normal stress, the highest level of anxiety was extremely severe anxiety, and the highest level of depression was normal depression.